2010
DOI: 10.1155/2010/535612
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Disturbances in Psoriasis: An Update

Abstract: Psoriasis is a common disease with the population prevalence ranging from 2% to 3%. Its prevalence in the population is affected by genetic, environmental, viral, infectious, immunological, biochemical, endocrinological, and psychological factors, as well as alcohol and drug abuse. In the recent years, psoriasis has been recognised as a systemic disease associated with numerous multiorgan abnormalities and complications. Dyslipidemia is one of comorbidities in psoriatic patients. Lipid metabolism studies in ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
110
2
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 130 publications
(165 reference statements)
5
110
2
13
Order By: Relevance
“…The substances are then further metabolized to FFAs, ceramides and cholesterol in the intercellular matrix. They are arranged in the form of a compact spatial structure and together with corneocytes and protein envelopes create a brick-and-mortar-like pattern, thus providing a protective barrier [9,10]. Multiple studies investigating psoriasis have shown abnormalities in the stratum corneum structure itself, along with impairment in the function of enzymes involved in lipid metabolism, resulting in changes in their composition, and increased epidermal exfoliation and TEWL [10][11][12][13][14].…”
Section: Lipidy W Naskórkumentioning
confidence: 99%
See 3 more Smart Citations
“…The substances are then further metabolized to FFAs, ceramides and cholesterol in the intercellular matrix. They are arranged in the form of a compact spatial structure and together with corneocytes and protein envelopes create a brick-and-mortar-like pattern, thus providing a protective barrier [9,10]. Multiple studies investigating psoriasis have shown abnormalities in the stratum corneum structure itself, along with impairment in the function of enzymes involved in lipid metabolism, resulting in changes in their composition, and increased epidermal exfoliation and TEWL [10][11][12][13][14].…”
Section: Lipidy W Naskórkumentioning
confidence: 99%
“…A high content of cholesterol has been found in skin scales shed in the process of psoriatic scaling. The skin of healthy individuals produces 85 mg of cholesterol a day, however patients with psoriasis lose 1-2 g of cholesterol with skin scales over the same period [9,15]. Vaccaro et al confirmed, both in vivo and in vitro, significant molecular and structural anomalies in the dermoepidermal junction in psoriatic lesions, potentially leading to abnormal keratinooraz chroni przed nadmierną utratą wody (transepidermal water loss -TEWL).…”
Section: Lipidy W Naskórkumentioning
confidence: 99%
See 2 more Smart Citations
“…Psoriasis is a relatively common chronic inflammatory and proliferative skin disease, with genetic and environmental aetiologies, that is characterized by abnormalities in skin lipids and increased production of inflammatory mediators [93,94].…”
Section: Psoriasismentioning
confidence: 99%